Rationale, Criteria, and Impact of Identifying Extreme Risk in Patients with Atherosclerotic Cardiovascular Disease - Yuhong Zeng; Dong Zhao; Tianyu Xu; Xiaoxia Fu (Cardiology Discovery)
Abstract. Assessment of the overall risk of atherosclerotic cardiovascular disease (ASCVD) is the first step in managing dyslipidemia and is an important reference for the target and intensity of treatment. Recently, different guidelines and consensuses on the management of this condition have successively recommended further risk stratification among patients with ASCVD, and a new “extreme risk” category has been proposed to identify patients who may obtain greater benefit from more intensive lipid-lowering therapy. The definition and terminology of extreme risk varies among different guidelines and consensuses; however, they all recommended an aggressive lipid-lowering therapeutic approach and/or a more stringent low-density lipoprotein cholesterol target for patients at extreme risk. Regardless of the definitions, this general approach may have a remarkable effect on the treatment of this condition in clinical practice. To help clinicians and patients to better understand the new strategy for the secondary prevention of ASCVD, this review provides a summary highlighting the necessity of further risk stratification among ASCVD patients, how patients at extreme risk can be identified, and the potential impact of applying the new “extreme risk” category in clinical practice.